Perceived effectiveness of endometriosis therapies on fatigue: an international survey - Kevin K W Kuan; Florian Heinzl; Andrew W Horne; Lucy H R Whitaker; Jana Heine; Christine Bekos (Reproduction and Fertility)
Current endometriosis treatments primarily focus on pain management, despite many patients also experiencing fatigue, which significantly impacts their quality of life. This study aimed to evaluate the perceived effectiveness of endometriosis treatments in managing fatigue. An international anonymous survey was conducted using the Qualtrics platform, with participants (aged 16 years and over) and a self-reported diagnosis of endometriosis. The survey collected demographic information, the brief fatigue inventory, and perceived impact of treatments on fatigue over the past 5 years. Ethical approval was granted by the Edinburgh Medical School Research Ethics Committee. Data analysis was performed using R, with results presented as medians and interquartile ranges. From 12 April to 25 May 2023, 2,907 responses were collected. Our results showed that fatigue was significantly worsened during menstruation (median: −2, IQR: −3 to −1) and slightly worsened during ovulation (median: −1, IQR: −2 to 0). Analysis revealed limited associations between common medical treatments, such as analgesics or hormonal therapy, and improvements in fatigue symptoms. Use of gonadotrophin-releasing hormone (GnRH) agonists was linked to a worsened fatigue, reported by 54% users. Surgical interventions and changes in rest patterns showed minimal improvement, while other behavioural modifications showed little to no effect. These findings suggest that current endometriosis treatments are largely ineffective in addressing fatigue. Limitations of this study include recall bias and confounding factors, which may influence perceived effectiveness of endometriosis therapies on fatigue. This underscores the need for more comprehensive management strategies to better support patients experiencing endometriosis-associated fatigue.